Local and remote forcing on the interannual variations of the sedimentary δ15N in Santa Barbara Basin during the past 80 years - Xu, Hanyue; Li, Da-Wei; Li, Hong-Chun; Zhao, Meixun; Berelson, William M.; Jin, Gui’e; Li, Li; Misra, Satabdi (Frontiers in Marine Science, 2022)
Sedimentary nitrogen isotope (δ15Nsed) in Santa Barbara Basin (SBB) has been mostly interpreted as the record of the eastern tropical North Pacific (ETNP) intermediate water denitrification process. Nevertheless, debate remains regarding sources and control mechanisms of δ15Nsed signal in SBB. Multi-proxy analyses including δ15Nsed, total organic carbon (TOC), total nitrogen (TN), C/N ratio, and marine biomarkers were performed on a 46-cm sediment core (SBB-190629) collected from SBB in 2019. The core was dated with varve counting and 210Pb dating method, showing a depositional history of 1938–2019 CE with a sedimentation rate of 0.564 cm/year. The findings show that the δ15Nsed record (at ~0.25-year resolution) ranges from 6.24‰ to 7.43‰, which was affected by both local and remote forcing. The long-term variations of the SBB δ15Nsed signature show a general decreasing trend from 1940 to the late 1980s, low values during 1980~2000, and an increase afterward, which is thought to reflect changes in ETNP denitrification induced by the strength of tropical trade winds. Our results also reveal a series of abrupt annual to multiannual changes, superimposed on the long-term variation mentioned above. The SBB local δ15N signal (Δδ15NSBB) is accessed by using the deviation from the mean δ15N (Δδ15N) of SBB-190629 to subtract the Δδ15N of the ETNP. The Δδ15NSBB record compares well with redox-sensitive proxies (Re/Mo ratio and C29 stanol/stenol ratio) from the SBB bottom water and with the OCmarine content calculated based on the C/N ratio mixing model, indicating that the Δδ15NSBB is mainly controlled by bottom water denitrification, which was induced by the change of upwelling intensity and marine productivity. Since various climatic factors (e.g., El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and North Pacific Gyre Oscillation (NPGO)) have different impacts on the upwelling intensity (hence the marine productivity and denitrification) in SBB on different timescales, the influence of combined climatic factors on SBB denitrification is time dependent.